Intersectoral Markup Divergence - Kristian Behrens; Sergey Kichko; Philip Ushchev (Center for Economic Studies and ifo Institute (CESifo), 2018)
We develop a general equilibrium model of monopolistic competition with a traded and a non-traded sector. Using a broad class of homothetic preferences—that generate variable markups, display a simple behavior of their elasticity of substitution, and nest the ces as a limiting case—we show that trade liberalization: (i) reduces domestic markups and increases imported markups in the traded sector; (ii) increases markups in the non-traded sector; and (iii) increases firm sizes in both sectors. Thus, while domestic and export markups in the traded sector converge across countries, markups diverge across sectors within countries. The negative welfare effects of higher markups and less consumption diversity in the non-traded sector dampen the positive welfare effects of lower markups and greater diversity in the traded sector.
Keywords: F12; F15; 330; monopolistic competition; variable markups; trade liberalization; non-traded goods; markup divergence